Spreadsheets : creating worksheets - Dinwiddie, Robert (London ; New York : Dorling Kindersley, 2000)
1. Microsoft Excel (Computer file). 2. Business - - computer programs. 3. Electronic Spreadsheets.
Includes index.
Faculty
Keywords: Microsoft Excel (Computer file); Business -- Computer programs; Electronic spreadsheets